The rose industry and the new rurban links: case study from east Africa - (:unkn) unknown (My University, 2013)
Panel New urban/rural linkages in a multi-polar Africa, mod. François Bart http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2036
Keywords: African Research